Advanced interstitial lung disease: Evidence-based management and clinical approach - Kattih, Zein; Greenstein, Zachary; Makkar, Priyanka; Gupta, Rohit (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Interstitial lung disease (ILD) is a heterogeneous group of diseases characterized by clinical, physiologic, and radiologic abnormalities. Advanced ILD (sometimes referred to as end-stage interstitial lung disease) is characterized by either gradual or rapid progressive decline of pre-existing or newly diagnosed ILD with worsening of symptoms, pulmonary function tests, six-minute walk test (6MWT) distance, and/or imaging findings, specifically high-resolution computed tomography (HRCT) imaging of the chest affecting patient’s quality of life. Special considerations are required for the management of patients with these advanced ILDs, particularly those who will ultimately require lung transplantation. Though several society and expert panels provide guidance on ILD management, there are none focused specifically on the approach to patients with advanced ILD. Objectives: In this review, we attempt to define advanced ILD and identify the clinical considerations required for diagnosis and management of patients with advanced ILD. Discussion: Pathophysiologic mechanisms of ILD and complications are not completely understood but include inflammation, fibrosis, pulmonary hypertension, venous thromboembolism, recurrent infections, and aspiration. Management of these patients includes consideration of anti-fibrotic medications, anti-inflammatory/immunosuppressive medications and treatment of concurrent pulmonary hypertension as indicated on a case-by-case basis. Non-pharmacologic management with supplemental oxygen, pulmonary rehabilitation, and palliative care are tailored to each patient’s clinical status. Finally, early referral to lung transplantation is critical, as advanced ILD can be fatal, and sometimes rapidly so. Conclusion: Advanced ILD is an oftentimes fatal group of heterogeneous diseases that have varying managements depending on underlying subtype. Identification of progressive disease and complications are the first steps to management of these patients to optimize lung function and quality of life and improve outcomes before lung transplantation.